A Survey on Green Supply Chain Management (GSCM) Challenges in the Malaysian Construction Industry - Syamimi Zulkefli, Nur; Mahmud, Fatimah; Mohd Zainudin, Nurhaizan (KnE Social Sciences, 2019)
In recent years, mounting environmental and sustainability concerns are driving the construction industry players to adopt green supply chain management (GSCM) in their organizations. GSCM is a converging sustainability approach that integrates environmental thinking and initiatives into the traditional supply chain management (SCM) practices. However, despite having various benefits, this approach has not been widely implemented. Therefore, this paper aims to reveal the challenges faced by Malaysian construction companies in implementing GSCM. A total of 160 questionnaires were distributed among contractors and consultants in Malaysian Construction Companies. Only 50 questionnaires completed by the respondents resulting in a response rate of 32%. The research found that leadership and commitment from top management as the main challenges among construction players in implementing GSCM, in addition to changing mindset and culture and government support and regulation. This finding will allow practitioners to acknowledge and prioritize the challenges embedded with GSCM implementation, thus come out with strategies to overcome the challenges. This research can be further enriched by including an in-depth study on the GSCM challenges through qualitative research.